2018
DOI: 10.1371/journal.pone.0192496
|View full text |Cite
|
Sign up to set email alerts
|

No maternal or direct effects of ocean acidification on egg hatching in the Arctic copepod Calanus glacialis

Abstract: Widespread ocean acidification (OA) is transforming the chemistry of the global ocean and the Arctic is recognised as the region where this transformation will occur at the fastest rate. Moreover, many Arctic species are considered less capable of tolerating OA due to their lower capacity for acid-base regulation. This inability may put severe restraints on many fundamental functions, such as growth and reproductive investments, which ultimately may result in reduced fitness. However, maternal effects may alle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In crustaceans, OA resulted in delayed gametogenesis and smaller spermatophores (Fitzer et al, 2012a;Cripps et al, 2014;Meseck et al, 2016;Conradi et al, 2019). OA did not affect copepod egg viability, oogenesis (Vehmaa et al, 2013;Thor et al, 2018), or barnacle and copepod gametogenesis (Smith et al, 2017;Pansch et al, 2018).…”
Section: Gametogenesis and Gamete Qualitymentioning
confidence: 93%
See 2 more Smart Citations
“…In crustaceans, OA resulted in delayed gametogenesis and smaller spermatophores (Fitzer et al, 2012a;Cripps et al, 2014;Meseck et al, 2016;Conradi et al, 2019). OA did not affect copepod egg viability, oogenesis (Vehmaa et al, 2013;Thor et al, 2018), or barnacle and copepod gametogenesis (Smith et al, 2017;Pansch et al, 2018).…”
Section: Gametogenesis and Gamete Qualitymentioning
confidence: 93%
“…Studies that measure hatch rate in brooders were limited to crustaceans and molluscs, as hatch rate was not reported for brooding species in any other taxa. Several brooding crustacean species held at low pH were found to have differences in fecundity, hatch success, or number of offspring Mayor et al, 2007;Findlay et al, 2009;Zhang et al, 2011;Vehmaa et al, 2012;Weydmann et al, 2012;Kita et al, 2013;Long et al, 2013;McConville et al, 2013;Zervoudaki et al, 2013;Cripps et al, 2014;Cao et al, 2015;Swiney et al, 2015;Thor and Dupont, 2015;Choi et al, 2016;Miller et al, 2016;Vehmaa et al, 2016;Borges et al, 2018a;Cardoso et al, 2018;Gravinese, 2018;Pansch et al, 2018;Thor et al, 2018;Lee et al, 2020). One study in copepods found that OA reduced the number of brooding females (Lee et al, 2019).…”
Section: Fecundity and Reproductive Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Runge et al (2016) found no effects of elevated CO 2 on vital rates of C. finmarchicus. Bailey et al (2017) determined that early life stags of C. glacialis were largely unaffected by increased CO 2 , and Thor et al (2018b) found no maternal or direct effects of ocean acidification on egg hatching for this species. Weydmann et al (2012) also found that CO 2 -induced seawater acidification had no significant effect on egg production of C. glacialis.…”
Section: Speciesmentioning
confidence: 98%
“…Although gametogenesis may remain unaffected or mediated by food supply as a consequence of near future environmental change, the viability of fertilization and larval development under projected environmental conditions could still compromise successful recruitment (Dupont et al, 2010b;Kroeker et al, 2010;Albright, 2011). Fertilization across taxa has often shown negative responses to increasing carbon dioxide and temperature (e.g., Kurihara et al, 2007;Ericson et al, 2012;Guo et al, 2015;Graham et al, 2015), but results are not always consistent between species (Clark et al, 2009), populations (Thor et al, 2018), sexes (Verkaik et al, 2016), or individuals (Campbell et al, 2016;Boulais et al, 2017). Meanwhile "carry-over" effects and transgenerational plasticity may affect subsequent life cycle stages (Parker et al, 2011;Kong et al, 2019), shifting the development "bottleneck" to later stages, or forcing tradeoffs with alternative reproductive traits such as fecundity or egg volume (Chakravarti et al, 2016).…”
Section: Discussionmentioning
confidence: 99%